Long term survival following cryoablation with adjuvant Toripalimab for anorectal malignant melanoma: a case report - Jiang, Xuejun; Ji, Zujin; Li, Peng; Yuan, Fangjun; Lei, Xinyi; Yang, Yong (Frontiers in Oncology, 2025)
BackgroundAnorectal malignant melanoma is a rare subtype of melanoma with a poor prognosis. Despite this, some patients decline Miles’ operation due to the sigmoid colostomies that follow abdominoperineal resections in cases of anorectal malignant melanoma.Case reportWe report the case of an 80-year-old woman diagnosed with anorectal malignant melanoma who underwent cryosurgery accompanied by adjuvant PD-1 therapy to maintain anal sphincter function. The results indicated that we successfully achieved the goal of sphincter preservation and therapeutic efficacy. The patient derived significant benefits from the cryoablation treatment.ConclusionsUltrasound-guided trans-anal cryoablation, when combined with adjuvant PD-1 therapy, offers a novel treatment approach for patients with anorectal malignant melanoma. Our results have confirmed the advantages of this treatment regimen, particularly for those desiring to retain anal sphincter function. Further studies are required to substantiate the efficacy of ultrasound-guided trans-anal cryoablation with adjuvant Toripalimab and to elucidate its underlying mechanisms.